Constructing an Explanation of Illness with Children: A Sample Case Study of Juvenile Arthritis. Issue 3 (2nd July 2016) - Capurso, Michele; Lo Bianco, Maria; Cortis, Elisabetta; Rossetti, Corrado
ABSTRACT: This study aimed to create a book to explain juvenile arthritis to newly diagnosed children, starting with the narratives of currently ill children. The development of the book followed a socio-constructivist approach and occurred over several stages, including: design of a comic-based workbook; conducting a workshop with ill children to listen to their experiences; collecting and organising the narratives into a children's book; adding physician explanations; consulting with parents and medical practitioners; and design of the final product. All stages led to meaningful enhancements to the book. The socio-constructivist approach and the workshop's open and friendly climate allowed children to express their conception of the illness, and to listen to and understand their peers' points of view. Paediatric practitioners contributed to the project, providing clarity to the book and ensuring it would be scientifically sound and usable within the paediatric setting. In conclusion, written material addressed to children needs to be developed with a systematic methodology which takes a proper account of children's voices. This can be achieved using a socio-constructivist approach and through an appropriate listening setting.